The Skyscraper Revolution: Global Economic Development and Land Savings - Gabriel M. Ahlfeldt; Nathaniel Baum-Snow; Remi Jedwab (Center for Economic Studies and ifo Institute (CESifo), 2023)
Tall buildings are central to facilitating sustainable urbanization and growth in cities worldwide. We estimate average elasticities of city population and built area to aggregate city building heights of 0.12 and -0.17, respectively, indicating that the largest global cities in developing economies would be at least one-third smaller on average without their tall buildings. Land saved from urban development by post-1975 tall building construction is over 80% covered in vegetation. To isolate the effects of technology-induced reductions in the cost of height from correlated demand shocks, we use interactions between static demand factors and the geography of bedrock as instruments for observed 1975-2015 tall building construction in 12,877 cities worldwide, a triple difference identification strategy. Quantification using a canonical urban model suggests that the technology to build tall generates a potential global welfare gain of 4.8%, of which only about one-quarter has been realized. Estimated welfare gains from relaxing existing height constraints are 5.9% in the developed world and 3.1% in developing economies.
Keywords: R11; R12; R14; R31; R33; O18; O13; 330; urban density; international buildings heights; skyscrapers; tall buildings; sustainable urbanization; city growth; commercial real estate; housing supply; urban sprawl; land savings; housing affordability; geographical constraints; environment